Significance of graphite inclusion occurrence in the minerals of the San Miguel skarn for the Palaeoproterozoic basement of Tandilia Belt (Argentina) and for the Río de la Plata Craton - Lajoinie, María Florencia (2019)
Graphite in Archaean-Palaeoproterozoic rocks has been a subject of interest since it could represent an evidence of early life on Earth. In the Palaeoproterozoic basement of the Tandilia Belt, graphite was found both in fluid inclusions (FI) hosted in the San Miguel skarn calc-silicate minerals, and as solid inclusions in calcite crystals from the protolithic marble (a¹³C enriched carbonate from the “Lomagundi-Jatuli event”). FI microthermometry and oxygen stable isotope ratios indicated the skarn minerals formation within the range of 630–650 °C (at ∼5 kbars) and ∼642–654 °C, respectively. Also, the characterisation of the metasomatic fluid (of a low salinity H₂O/NaCl KCl H₂O aqueous system) pointed out that the zonal crystallisation pattern shown by the skarn minerals (wollastonite-vesuvianite, grossular-diopside-calcite and diopside-calcite zones in the exoskarn, and grossular-diopside and diopside-calcic plagioclase zones in the endoskarn) responds to the increase of the involved cation activity gradients (Ca²⁺-Si4⁺-Mg²⁺-Fe²⁺/³+-Al³⁺) and not to significant changes in the temperature or concentration of CO₂ in the system. Variation in the crystallinity degree of the graphite hosted in the skarn minerals and in marble calcite, shown by Raman spectroscopy, would indicate that the graphite could have been formed from the ripening of organic matter present in the sedimentary rocks during the metamorphic-metasomatic event (Transamazonian Orogeny). In this sense, the increase of the organic carbon productivity in the oceans during the Palaeoproterozoic, represented by the “Lomagundi-Jatuli event”, would support this graphite origin and also the possible existence of a marine sedimentary basin in the previous stages of the Rio de la Plata amalgamation (Siderian-Rhyacian), in the San Miguel area of the Tandilia Belt.